Specificity and sensitivity of biotinidase activity measured from dried blood spot by colorimetric method (Annals of Medical Research, 2021)
Aim: A variety of methods are used to determine biotinidase activity (BA), such as different substrates, biological samples, and analytical techniques. In this study, we aimed to discuss the specificity and sensitivity of the fluorometric method used in the measurement of biotinidase activity in the newborn screening program (NSP) in Turkey.Material and Methods: Medical records of 164 patients who were referred to our clinic with the diagnosis of biotinidase deficiency (BD) from primary health care institutions were evaluated retrospectively. According to this classification, those with normal BA were included in the negative group and those with partial or profound BD were included in the positive group.Results: Four patients had profound and 66 patients had partial BD, whereas 94 patients had normal BA. ROC analysis was performed to determine the specificity and sensitivity of BA from dry blood spot. Analysis showed 41% sensitivity and 39% specificity for BA≥56.91 MRU (AUC: 0.339, p 0.001). Conclusion: TIt was thought that low efficacy of fluorometric method used for the diagnosis of BD in the NSP may cause diagnostic delay. It is thought that a more effective neonatal screening program can be applied by using tandem mass spectrometer method.
Keywords: Biotinidase deficiency; fluorescence; inborn errors of metabolism; neonatal screening.